Penilaian kenyamanan termal pada bangunan perpustakaan Universitas Bandar Lampung - Ai Siti Munawaroh; Rivena Elbes (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Thermal comfort assesment of Universitas Bandar Lampung library’ building The library building has not yet gained a respectable place in the local government, schools, and universities. Library buildings are generally not prioritized and not in strategic location. Though the purpose of a building is to accommodate activities and to provide comfort for its users. For this reason, there is a need for research on comfort, especially thermal comfort in that building. The research method in this study is to make direct measurements on the object of the research and distribute the questionnaire. Direct measurement using a thermometer, anemometer, and hygrometer. At the same time the distribution of questionnaires was carried out to the visitors. The purpose of this study is to find out: 1) Thermal comfort levels in the buildings and 2) What aspects affect thermal of the building. The results of the study were obtained: 1) The level of thermal comfort in the Universitas Bandar Lampung’ library building can be concluded comfortably, based on the results of measurements of temperature, humidity, and wind speed. Based on the results of visitor perceptions obtained through filling out the questionnaire sheet, as many as 60% of visitors thought the conditions were comfortable and 40% thought it was very comfortable. 2) Aspects that influence thermal comfort in the Universitas Bandar Lampung’ library building based on the results of measurements using measuring instruments and perceptual values using a questionnaire include: a). Temperature b). Humidity c). Number of visitors, and d). Clothes. © 2019 Rivena Elbes, Ai Siti Munawaroh